The Impact Of Audit Fee, Size Of Public Accounting Firm, Company Size, And Leverage On The Communication Of Key Audit Matters (Implementation Of The First Year Of KAMs Adoption In Independent Auditors' Reports In Indonesia) - Widya Sania; Syahril Ali (Eduvest - Journal of Universal Studies, 2024)
Auditing standard 701 "Communicating Key Audit Matters (KAMs) in the Independent Auditor's Report" will be implemented in Indonesia in 2022. The communication of KAMs aims to increase the transparency of financial statements for users. This study examines the effect of audit fees, Size of public accounting firm, company size and leverage on the communication of Key Audit Matters (KAMs). The research population is companies that are listed on the Indonesia Stock Exchange and report audited financial statements for the fiscal year 2022. The sample was selected using purposive sampling method. The research data was processed using the Multiple Linear Regression method using IBM SPSS Statistics software ver. 25. This study proves that audit fees (sig 0.000 < 0.05) and Size of public accounting firm (sig 0.000 < 0.05) have a positive and significant effect on communicating KAMs. While company size (0.188 > 0.05) leverage (0.378 > 0.05) has no significant effect on communicating KAMs. Based on the results of the study, it is hoped that companies can consider an adequate audit fee budget and choose a Public accounting firm whose competence is in accordance with the conditions of the company to be able to increase the communication of KAMs. Thus, companies can increase investor and other stakeholder confidence through the communication of KAMs as an effort to demonstrate commitment to transparency and good corporate governanc